Bibliometric trends and patterns in Tasar silkworm (Antheraea mylitta) research: a data report (1980–2024) - Komal, J.; Gowrisankar, R.; G. V., Vishaka; Nadaf, H.; Samal, Ipsita; Dinesh Kumar, Pasumarthi Venkata; Selvaraj, C.; Reddy, B. Thirupam; Selvakumar, T.; Mahanta, Deepak Kumar; Bhoi, Tanmaya Kumar (Frontiers in Insect Science, 2025)
This study presents a bibliometric analysis of publication trends in Tasar silkworm (Antheraea mylitta) research from 1980 to 2024. A comprehensive search was conducted using the Scopus database with keywords related to Tasar silkworm. A total of 741 relevant articles were identified and analyzed using VOSviewer, Bibliometrix, and Biblioshiny in R to examine statistical patterns. Over the decades, research focus has transitioned from fundamental silk characterization to biomedical applications, including tissue engineering, biodegradation studies, and antioxidant properties. Publication trends indicate peak research activity between 2007 and 2010, followed by a decline post-2018, likely due to shifting priorities toward commercially dominant silkworm species. Indian institutions have been the primary contributors, reflecting strong domestic expertise, while global collaborations remain limited. Keyword analysis highlights the growing interdisciplinary nature of Tasar silk research, extending into biomaterials and sustainable technology. Future research directions emphasize biotechnological advancements, biomedical applications, eco-friendly processing, climate resilience, and commercialization strategies. Strengthening international collaborations and integrating innovative technologies will be crucial for advancing Tasar silk research in both scientific and industrial domains.